POLARRIS: A POLArimetric Radar Retrieval and Instrument Simulator. Issue 8 (18th April 2019) - Matsui, Toshi; Dolan, Brenda; Rutledge, Steven A.; Tao, Wei‐Kuo; Iguchi, Takamichi; Barnum, Julie; Lang, Stephen E.
Abstract: This paper introduces a synthetic polarimetric radar simulator and retrieval package, POLArimetric Radar Retrieval and Instrument Simulator (POLARRIS), for evaluating cloud‐resolving models (CRMs). POLARRIS is composed of forward (POLARRIS‐f) and inverse (retrieval and diagnostic) components (iPOLARRIS) to generate not only polarimetric radar observables ( Z h, Z dr, K dp, ρ hv ) but also radar‐consistent geophysical parameters such as hydrometeor identification, vertical velocity, and rainfall rates retrieved from CRM data. To demonstrate its application and uncertainties, POLARRIS is applied to simulations of a mesoscale convective system over the Southern Great Plains on 23 May 2011, using the Weather Research and Forecasting model with both spectral bin microphysics (SBM) and the Goddard single‐moment bulk 4ICE microphysics. Statistical composites reveal a significant dependence of simulated polarimetric observables ( Z dr, K dp ) on the assumptions of the particle axis ratio (oblateness) and orientation angle distributions. The simulated polarimetric variables differ considerably between the SBM and 4ICE microphysics in part due to the differences in their ice particle size distributions as revealed by comparisons with aircraft measurements. Regardless of these uncertainties, simulated hydrometeor identification distributions overestimate graupel and hail fractions, especially from the simulation with SBM. To minimize uncertainties in forward model, the particle shape and orientation angle distributions of frozen particles should be predicted in a microphysics scheme in addition to the size distributions and particle densities. Key Points: New polarimetric radar simulator was developed for CRM evaluation There are uncertainties remained in the assumptions of axis ratio and canting angles of ice particles Hydrometeor identification allows robust evaluation for bulk and bin microphysics